Implementasi Lean Warehousing untuk Meningkatkan KPI di PT. TXL - Taqwanur (2477 - 6165, 2021)
PT. TXL is a company engaged in the warehouse sector by distributing its products to the East of Indonesia area. The smooth and reliable operation of a warehouse is strongly influenced by its effective, efficient and reliable activities with continually improvement. One of the challenges for the warehouse role is to shorten the process time required by accelerating working time, increasing efficiency, and increasing work effectiveness. Performance of PT. TXL is measured using Key Performance Indicators (KPI) are productivity and the number of complaints, so the total process time can be improved. The total process time the initial condition is 7 hours 3 minutes with the stages of the process including Sales Orders, Picking, Sorting, Packing, Dispatching and Delivery. By using the Lean Warehousing method, Value Adding Activity (VAA), Necessary but Non-Value Adding Activity (NBNVAA) and Non-Value Adding Activity (NVAA) can be identified through questionnaires and brainstorming by senior employees and leaders. The focus of improvement is to reduce waste in extra processing, motion, overproduction and waiting. After improvement were done, the total process time decreased to 3 hours 48 minutes with Non-Value Adding Activity time decreased from 3 hours 17 minutes to 37 minutes. This has another impact on increasing KPI are productivity increasing by around 45% and the number of complaints per mount decreasing at the end of October 2021 to 2 complaints.